(untitled) (International Journal of Food and Nutritional Sciences, 2022)
“Securitization And Reconstruction of Financial Assets and Enforcement of Security Interest Act” (SARFAESI ACT ) 2002 is the law’s full name. In India, it gives banks and financial institutions the freedom to seize non -performing assets (NPAs), enforce their security interest in those assets, and sell those assets to pay off their debts all without the need for court innervation. The SARFAESI Act 2002 enables banks and other financial institutions to recoup loans from defaulting borrowers by selling commercial or residential assets at auction.